Penerapan Estimasi Waktu Produksi Pada Aplikasi Jual-Beli Buku Online - Amrizal Rizky Fajar; Endra Rahmawati; Anjik Sukmaaji (Jurnal Sistem Informasi Universitas Dinamika, 2022)
CV. Arlina is a company engaged in the printing and publishing of books. In this modern era CV. Arlina has problems in reaching their consumers (schools) who are outside the Surabaya area other than through sales. After the consumer (school) CV. Arlina made an order, CV. Arlina will provide an estimate of how long it will take to produce the book. The problem comes when it turns out that the initial estimate assumption does not match the length of production time that occurs. This results in an increase in queuing time for further orders. Another quite fatal problem that has ever happened is that the incoming order list is only recorded on paper, this allows CV. Arlina accidentally missed one of the orders. This will result in this order being processed immediately and temporarily suspending other orders. The solution given to the above problems is to build a website application that aims to help market the books issued by CV. Arlina, as well as developing an application that can manage incoming sales and orders by applying production time estimation and production scheduling using the First Come First Serve method. Estimated production time will aim to find the estimated time required for the company to complete a job based on the company's ability. Production scheduling with the First Come First Serve method aims to plan production and manage work based on the work that comes in first. With the estimated production time and production scheduling, CV. Arlina and their customers (schools) can know how long it will take for the order to be processed. Base of the research testiog outcome using UAT (User Acceptance Testing), it shows that 47.57% users agree and 51.43% users strongly agree with the admin application, while 20% users agree and 80% users strogly agree with the main website application.